2011
DOI: 10.1371/journal.ppat.1001301
|View full text |Cite
|
Sign up to set email alerts
|

The Genotype of Early-Transmitting HIV gp120s Promotes α4β7 –Reactivity, Revealing α4β7+/CD4+ T cells As Key Targets in Mucosal Transmission

Abstract: Mucosal transmission of HIV is inefficient. The virus must breach physical barriers before it infects mucosal CD4+ T cells. Low-level viral replication occurs initially in mucosal CD4+ T cells, but within days high-level replication occurs in Peyer's patches, the gut lamina propria and mesenteric lymph nodes. Understanding the early events in HIV transmission may provide valuable information relevant to the development of an HIV vaccine. The viral quasispecies in a donor contracts through a genetic bottleneck … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
171
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(178 citation statements)
references
References 67 publications
7
171
0
Order By: Relevance
“…We and others have reported that founder viruses generally have fewer glycosylation sites and more compact Envs (9,(31)(32)(33), and our earlier studies also demonstrated that newly transmitted viruses were not escape variants from PL-neutralizing antibodies in the donor (9). Recent studies have suggested that subtype A and C founder viruses bind efficiently to the gut homing receptor α4β7 expressed on a subset of highly susceptible CD4 T lymphocytes and that this property can be reduced with evolution of the virus after transmission (34). Collectively, the current study and these previous studies point to selection for a virus variant with a set of essential biological properties during transmission.…”
Section: Discussionmentioning
confidence: 61%
“…We and others have reported that founder viruses generally have fewer glycosylation sites and more compact Envs (9,(31)(32)(33), and our earlier studies also demonstrated that newly transmitted viruses were not escape variants from PL-neutralizing antibodies in the donor (9). Recent studies have suggested that subtype A and C founder viruses bind efficiently to the gut homing receptor α4β7 expressed on a subset of highly susceptible CD4 T lymphocytes and that this property can be reduced with evolution of the virus after transmission (34). Collectively, the current study and these previous studies point to selection for a virus variant with a set of essential biological properties during transmission.…”
Section: Discussionmentioning
confidence: 61%
“…23,24,36,[65][66][67] Rolland et al have reported that sieve mutations in HIV-1 breakthrough infections in RV144 contain mutations at positions 169 and 181 in V2. 50 T cell epitope mapping studies using PBMCs from HIV-1-uninfected RV144 vaccine recipients and the interferon-gamma ELISpot assay also showed preferential targeting of the V2 loop and that the responding cells were CD4…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, infected T cells could migrate to different body compartments to deliver virus. Finally, it has been suggested that the viral Env protein in the transmitted virus acts as a mimic of a4b7 integrin to target virus to CD4 þ T cells in the GALT (Nawaz et al 2011); a corollary of this model is that viruses without this feature might initiate a local mucosal infection but not establish a systemic infection because of failure to traffic to the GALT. If stable infections were failing because of an absence of the ability to mimic a4b7 integrin to target GALT one might expect to see seroconversion based on transient replication in the proximal mucosal tissues, as is seen for HSV-2 infection, but this is not observed for putative abortive HIV-1 infections.…”
Section: Early Events In Replicationmentioning
confidence: 99%